Kontexte kreativen Schreibens Eine Standortbestimmung in Theorie und Praxis - Willms, Weertje; Backes, Martina (Frank & Timme, 2021)
Creative writing is booming: in writing institutes, adult education centers and schools, in therapy and integration work, as well as in writing workshops for amateurs. Universities in German-speaking countries are also are also discovering creative writing as a subject for further education and training. Contexts of Creative Writing provides a comprehensive overview of the diverse fields of creative writing and sheds light on both theory and practice. Thus, alongside contributions from various academic disciplines - such as didactics, linguistics, literary studies, media studies and medicine - there are also reports from social work, schools or the cultural sector. The spectrum of the presentations ranges from theoretical discussions and conceptualization to insights into writing workshops at various institutions and the presentation of concrete teaching models.